2006
DOI: 10.1111/j.1600-051x.2006.01014.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of controlled immediate loading and implant design on peri‐implant bone formation

Abstract: Well-controlled immediate implant loading accelerates tissue mineralization at the interface. Adequate bone stimulation via mechanical coupling may account for the larger bone response around the screw-type implant compared with the cylindrical implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 40 publications
5
60
1
Order By: Relevance
“…Secondly, we evaluate how the implant geometry can affect the formation of bone, not only by changing the stresses and strains of the surrounding tissue, what has been experimentally verified (Vandamme et al, 2007), but also by altering certain biological phenomena, such as growth factor diffusion or the direction of cell migration.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…Secondly, we evaluate how the implant geometry can affect the formation of bone, not only by changing the stresses and strains of the surrounding tissue, what has been experimentally verified (Vandamme et al, 2007), but also by altering certain biological phenomena, such as growth factor diffusion or the direction of cell migration.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…Implant design features such as thread pitch, thread geometry, helix angle, thread depth and width may also affect implant stability (Abuhussein et al 2010). The screw or "threaded" design minimises implant micromotion during function ) and also increases the surface area of the implant for bone-to-implant contact, compared to cylindrical implants (Vandamme et al 2007). Additionally, tapered implant designs bring higher primary stability than straight cylindrical implant geometry as they may provide a degree of compression of the cortical bone in a poor bone implant site (O 'Sullivan et al 2004b).…”
Section: Implant Geometrymentioning
confidence: 99%
“…Vandamme et al found that the BFA was larger in loaded versus unloaded implants and found a higher value in those subjected to an a�ial displacement of 90 µm (9,12). A significant difference in application time between loaded and non-loaded implants was reported by these authors but was not observed by Duyck et al (13).…”
Section: Response Of Peri-implant Bone In Implants With Conresponse Omentioning
confidence: 91%
“…Vandamme et al (9,10,12) found a higher B�C value in loaded versus non-loaded implants. �n contrast, Duyck et al reported a lower B�C value in loaded implants, using a similar study design and duplicating the load cycles, suggesting that a loading of less than 800 cycles produces an increase in the B�C, although the e�act limit was not defined (15).…”
Section: Response Of Peri-implant Bone In Implants With Conresponse Omentioning
confidence: 96%
See 1 more Smart Citation